Peran Kelembagaan Adat Dalam Pengadaan Lahan Untuk Pembangunan di Kota Sentani Kabupaten Jayapura Provinsi Papua - Ondikeleuw, Haery M.; Ma'rif, Samsul (Magister Pembangunan Wilayah dan Kota,Undip, 2015)
The development of Sentani city post defined as district capital of Jayapura has privilege or growth rapidly. Implication as a new city as result transfer district capital from Jayapura city is on increase land need.. Land supplying to support development activity with acredibity is constreuned by tradition land tenure for Sentani city, tradition land is customary rights from three villages, than is Sereh, Yobeh and Ifar Besar village. Based on this background, so issue land supplying is on how tradition institution role in land supplying to development in Sentani city. By using description-qualitative method with land use distribution activity analysis, customaty rights analysis, comparasion procedure and tradition land release process between tradition people perspective and positive law and also tradition institution involvement analysis, obtained findings that tradition institution role still limited role, not opmimal. Not optimal tradition institution as a reslt of coordination effectiveness, integration, synchronization, Â simplification , mechanism (KISSME) has not been adequate, tradition institutional have not been up duties and responsibilities as protector, protective, attendant, antor, supreme leader of existing norms.